Epilepsy imitator: tongue biting caused by sleep-related facio-mandibular myoclonus. (October 2020) - Zhang, Sheng; Aung, Thandar; Lv, Zhijun; Zhao, Xiaoyu; Wang, Peng; Shi, Tianming; Guo, Shunyuan; Geng, Yu; Jin, Bo
Abstract: Purpose: Sleep-related facio-mandibular myoclonus(SRFMM) is a rare and under-recognized stereotyped parasomnia. SRFMM can present with isolated tongue biting, which can be misdiagnosed as epilepsy and sleep bruxism. We aimed to investigate the clinical characteristics and demographics of patients with SRFMM. Methods: We reported a case of SRFMM and presented a literature review on SRFMM. We searched the Medline, Pubmed, and Web of Science database using the following search algorithm: "facio-mandibular myoclonus" or "masticatory myoclonus" or "tongue biting" limited to publications in English. Results: In total, nine studies were included. In addition to our case, a total of 17 patients were analyzed. SRFMM was found to be more prevalent in males, with a mean age of 48.2 years old. Most of the patients experienced tongue biting during non-rapid eye movement sleep. A majority of the patients were misdiagnosed with epilepsy or sleep bruxism. The simultaneous video EEG and surface EMG was beneficial in confirming the diagnosis of SRFMM. In some patients, clonazepam was reported to ameliorate the tongue biting event. Conclusion: This study represents a comprehensive summary of SRFMM, which has unique clinical features. Extra-caution may be needed in these cases as it may puzzle neurologists in terms of management.